2022
DOI: 10.3390/ma15155174
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Passivation of the Surface of Candidate Materials for MSR by Adding Oxygen Ions to FLiNaK Salt

Abstract: The problem of tailoring the structural materials for MSR is solved by continuously overcoming the shortcomings of widely used materials and finding new ones. The materials commonly used in engineering may not be applicable for MSR due to their high corrosivity. Experiments were carried out to determine the corrosion rate of stainless steel 12Cr18Ni10Ti with different concentrations of oxide ions (by adding lithium oxide to the melt in the concentration range from 0 to 0.8 wt.%) in a FLiNaK melt. The formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…At the same time, special requirements are imposed regarding the quality of prepared fluoride melts to be used as a working medium in MSRs [1,12,13]. Particular attention is paid to oxygencontaining impurities due to their significant effect on corrosion processes [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, special requirements are imposed regarding the quality of prepared fluoride melts to be used as a working medium in MSRs [1,12,13]. Particular attention is paid to oxygencontaining impurities due to their significant effect on corrosion processes [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that chromium, iron, and nickel in the composition of the construction alloys may be subjected to corrosion in FLiBe and FLiNaK salts [15][16][17][18][19][20]. The corrosion rate of these materials depends on the presence of different admixtures, such as oxides and hydroxide ions [21,22], HF [22], and metals fluorides (for instance, CrF 3 , NiF 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…% of Li 2 O showed a larger weight loss than that corroded by FLiNaK without Li 2 O 10 . Karfidov et al also reported that the corrosion rate of 12Cr18Ni10Ti steel in FLiNaK with a concentration of O 2− <200 ppm was larger than that in FLiNaK with 500 ppm of O [2][3][4][5][6][7][8][9][10][11] . Yang also observed Cr and Mn oxides formed near the grain boundaries of SS316H attacked by thermally purified NaF-KF-UF 4 salt (FUNaK), indicating the interactions between oxides and metals 12 .…”
mentioning
confidence: 99%